Efficiency of Organo-Mineral Fertilizer Enriched with Citric Acid in Corn (Zea Mays L.) grown in the Greenhouse (Research, Society and Development, 2020)
This research aimed to evaluate the effect of organomineral fertilizer enriched with citric acid, on accumulation of dry matter content and phosphorus (P) in maize plants grown in greenhouse. A randomized block design with 6x3 factorial was used, combining six P sources (triple superphosphate, natural reactive phosphate of Bayóvar, superphosphate + poultry litter, Bayóvar phosphate + poultry litter, superphosphate + poultry litter + citric acid, Bayóvar phosphate + poultry litter + citric acid), three applied P levels (40, 80 and 120 kg ha-1 of P2O5), with four repetitions. The organomineral fertilizers produced with superphosphate provided higher accumulation of dry matter and P in shoots of maize plants than the organomineral fertilizers with Bayóvar phosphate. Plants that received the organomineral fertilizers with superphosphate presented higher accumulation of biomass and P in shoots than plants that received solely superphosphate, without effect of citric acid. The citric acid added to the organomineral fertilizer produced with natural reactive Bayóvar phosphate increased the accumulation of P in roots. The incorporation of organic matter to triple superphosphate increases maize growth and that the addition of citric acid to the organomineral fertilizers produced with natural phosphate increases the root growth.